Perilaku prososial siswa reguler di sekolah inklusi: Bagaimana peranan relasi guru – siswa? - Athiyyah Nadiawan Ramadhani; Suroso; Isrida Yul Arifiana (INNER: Journal of Psychological Research, 2023)
Abstract The study aims to know the relationship between teacher-student relations and regular student prosocial behavior at the inclusion school. The hypothesis suggests that there is a positive relationship between teacher relatives-student and regular student prosocial behavior. The design of this study USES a correlational quantitative study method. The study was conducted with as many as 170 regular students at the X Surabaya junior high school and an age span of 13-17. The instruments used in the study are the prosocial behavior scales consistent with the Eisenberg & Mussen theory (1989) and the teacher’s relative students match the pianta theory (2001). The data obtained is then analyzed using product moment analysis techniques with the help of SPSS 24 for Windows. Based on the results of the data analysis already obtained results that there is a positive and significant connection between teacher relative-students with a prosocial behavior of rxy = 0.641 on p = 0,000 (p < 0.01). The acceptance of hypotheses in this study suggests that teacher relatives-students strongly relate to the regular student’s prosocial behavior. The higher the teacher-student then the higher the regular prosocial behavior of the regular student, as the lower the teacher’s relative-the student then the lower the regular prosocial behavior of the institution school. Keywords: Inclusion School, Prosocial Behavior, Regular Students.